Andrographis paniculata Leaf Extract Increases Interleukin-2 in Malnutrition Rat Model - Dwiningsih, Fortuna; Natzir, Rosdiana; Ilhamuddin, Ilhamuddin; Yustisia, Ika; Sulfahri, Sulfahri (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Malnutrition is a global health concern that results in changes in nutritional status, as indicated by alterations in phenotypic markers, hematological and biochemical parameters, and increased susceptibility to infection, as shown by decreased interleukin (IL)-2 levels. Andrographolide, the active component of Andrographis paniculata, stimulates the immune system and exhibits antibacterial and antiviral activity. Therefore, A. paniculata may serve as a potential adjuvant therapy for malnutrition. This study was conducted to analyze the effect of A. paniculata as an immunomodulator against malnutrition with characteristics of environmental enteric dysfunction (EED) and a low-protein diet by examining phenotypic markers, hematological, biochemical, and IL-2 levels.METHODS: Forty-five male Wistar rats were divided into seven groups. They were fed either a standard or a low-protein diet before receiving oral administration of various concentrations of A. paniculata leaf extract (APLE). APLE was administered 21 days after the initial low-protein diet. Hematological, biochemical, and phenotypic markers were assessed to determine the nutritional status of the rats. The protective effects of APLE were evaluated by measuring IL-2 levels using enzyme-linked immunosorbent assay (ELISA).RESULTS: Malnourished rats exhibited slow body growth, physical and behavioral changes, reduced leukocyte count, total protein, albumin, cholesterol, and villi length. Malnourished rats treated with APLE showed a more effective and significant increase in IL-2 levels, with higher concentrations of APLE resulting in higher IL-2 levels.CONCLUSION: APLE, in a concentration-dependent manner, can increase IL-2 levels, suggesting that APLE may have potential protective effects in a rat model of malnutrition.KEYWORDS: Andrographis paniculata, environmental enteric dysfunction, interleukin (IL)-2, low protein, malnutrition